The effect of the morphological formula in changing the linguistic meaning - أحمد, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The purpose of the research is to prove the importance of the morphological meaning in giving a certain linguistic meaning and how this meaning changes by changing the structure of the word. The research emphasizes two ideas. The first is proving the morphological meaning of the word “yotekonh” . In the context of Quran Allah imposes fasting on the believers who can fast and for those who can’t to pay money. By reading the word morphologically another meaning appears. The second is proving the effect of the different morphological formula of the of the word “sokhriya” in sur Al Zukhruf and Al Mo’mnoon in changing the linguistic meaning.